Cannibales ante portas: стратегія критичного описання постмодерністів в сучасном у англомовному світі - Осіпян, О. (Інститут історії України НАН України, 2008)
This article is about perception of post modernism by the conservative reading public in the US, UK, Canada and Australia. Post modernist rejection of the progress, nation -state, modern concept of time and author, the leading role of Western civilization etc., tur ned attention to the marginalized groups such as slaves, women, gays (in case of the US also natives and Afro-Americans) and other minorities. The impact of post modernism produced new research agenda and teaching courses generally known as “cultural studi es”. According to post modernists – mostly literary critics and social theorists – history is only a part of the bourgeous society discourse used to suppress subaltern groups. In the 1990s professional historians made an effort to reply on the post moderni st challenge. The author analyses the readers’ reviews on the Keith Windschuttle’s book “The Killing of History” (firstly published in 1994). These reviews were written down on the www.amazon.com web site in 1999-2006. Readers – mostly supporters of the traditional empirical history/conventional national history – criticised post modernism and cultural studies as “the disease” of relativism and scepticism. For the conservative right oriented public history is a fixed set of facts, and revisionism – the substitution of new viewpoints for old – as dangerous action of the left wing intellectuals. Describing post modernists and their writings conservative readers unconsciously used terms concerned with the concepts of triba lism and barbarianism in order to avoid equal discussion with the “promoters of nonsense” speaking in “the barbarous jargon”.